Ensileability of alfalfa: cutting, maturity and treatment effects - J.L. Curtis; C. Lin; K.K. Bolsen (Kansas Agricultural Experiment Station Research Reports, 1990)
Analysis of ensiling characteristics from late-bud, 10% bloom, and 50% bloom alfalfa, taken within each of four cuttings identified higher pre-ensiled dry matter (DM) content during the first two cuttings, whereas crop buffer capacity was weakest during the third cutting and subsequently strongest throughout the fourth cutting. Initial pH was lowest at the first cutting and increased with each cutting thereafter. Dry matter increased linearly within maturity, whereas late-bud maturity had the highest buffer capacity and initial pH. From hr 24 until d 90, the pH values were consistently highest for late-bud and lowest for 50% bloom silage. 1featments receiving 2% dextrose showed a slightly higher DM. At each of seven laboratory silo opening times, a combination of added dextrose and a lactic acid bacteria inoculant yielded the lowest pH; inoculant alone gave the next lowest pH values through hr 48. From d 3 to 90, pH's were consistently highest for control silages, followed by inoculant. dextrose, and dextrose + inoculant combined.
Keywords: Cattlemen& #x27; s Day; 1990; Kansas Agricultural Experiment Station contribution; no. 90-361-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 592; Beef; Alfalfa; Silage; Inoculant; Dextrose